DNA Methylation and Plants Response to Biotic and Abiotic Stress - Bhattarai, Kushal; Poudel, Mukti Ram (Trends in Sciences, 2022)
DNA methylation is a conserved epigenetic modification that regulates, stabilizes, and maintains genomic integrity. Loss of DNA methylation or aberrant patterns of DNA methylation causes abnormalities in the gene regulation of plants. DNA methylation in plants is regulated by the combined action of de novo methylation, maintenance of methylation, and demethylation. The enzymes that regulate DNA methylation in plants are different but have some homology to that of mammalian DNA methylation enzymes. DNA methylation helps to develop adaptation mechanisms towards various biotic and abiotic stresses. This paper provides a comprehensive review of the DNA methylation pathway and its role in biotic and abiotic stress tolerances in plants. HIGHLIGHTS Plants responds to the changing climatic condition via epigenetic changes - changing the gene expression patterns, without changing the DNA sequences Abiotic and biotic stress leads to the differential expression of genes; furthermore, plants have memory in the form of epigenetic marks laid in the DNA sequences DNA methylation in plants is regulated by the combined action of de novo methylation, maintenance of methylation, and demethylation GRAPHICAL ABSTRACT